ECONOMIC FOUNDATIONS ΤΟ ASSESS NON-MARKET VALUES IN MARINE AND COASTAL ECOSYSTEMS’ WATER QUALITY - HALKOS, George E.; GALANI, Georgia K. (Journal of Environmental Management and Tourism, 2016)
Marine and coastal ecosystems are of high importance owing to the mankind dependence on the goods and services provided. Due to the lack of an official market to valuate non-marketed goods and services, contingent valuation is applied intensively in order to provide the policy makers and the society generally with the specific values derived by a developed hypothetical market. As water quality is one perspective of healthy marine and coastal ecosystems, the aim of this study is to review the theoretical framework in accordance with the existing statistical models to estimate the welfare measures and the numerous disadvantages that have to be taken into account in order to implement a reliable contingent valuation survey. This will help the decision maker to implement and follow the right steps in any valuation effort.
Keywords: contingent valuation; willingness to pay or to accept (WTP/WTA); marine and coastal ecosystems